2015
DOI: 10.1111/nan.12219
|View full text |Cite
|
Sign up to set email alerts
|

The enzymatic activities of brain catechol‐O‐methyltransferase (COMT) and methionine sulphoxide reductase are correlated in a COMT Val/Met allele‐dependent fashion

Abstract: Aims The enzyme catechol-O-methyl transferase (COMT) plays a primary role in the metabolism of catecholamine neurotransmitters and is implicated in the modulation of cognitive and emotional responses. The best-characterized single nucleotide polymorphism (SNP) of the COMT gene consists of a valine (Val)-to-methionine (Met) substitution at codon 108/158. The Met-containing variant confers a marked reduction in COMT catalytic activity. We recently showed that the activity of recombinant COMT is positively regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 72 publications
2
10
0
Order By: Relevance
“…Qualitative synthesis showed that findings were inconsistent, were not replicated, or lacked statistical evidence to substantiate reported genotype differences (Table S11 in Supplement 2). (20)(21)(22)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)…”
Section: No Consistent Evidence For Functional Polymorphisms In Dopammentioning
confidence: 99%
“…Qualitative synthesis showed that findings were inconsistent, were not replicated, or lacked statistical evidence to substantiate reported genotype differences (Table S11 in Supplement 2). (20)(21)(22)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)…”
Section: No Consistent Evidence For Functional Polymorphisms In Dopammentioning
confidence: 99%
“…The present study was conducted on the same postmortem brain tissues used in a previous study (Moskovitz et al, 2015). All demographic and clinical characteristics of the individuals are described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted from brain tissue and COMT rs4680 genotyping was performed as previously indicated (Moskovitz et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations